The relationship among self-care, glycemic control, and quality of life in Indonesian patients with type 2 diabetes mellitus: An exploratory structural equation modeling study - Malini, Hema; Kardila, Intan Yullya; Alhofaian, Aisha (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: The relationship between self-care behaviors, physiological indicators, and quality of life (QoL) in Type 2 Diabetes Mellitus (T2DM) remains underexplored in Indonesian populations. Understanding these factors is crucial for designing culturally appropriate interventions. Objective: To examine the direct effects of four self-care domains on QoL and the potential mediating roles of HbA1c, blood pressure, and BMI among Indonesian patients with T2DM. Methods: A cross-sectional exploratory study was conducted August to September 2022 among 128 purposively selected patients from community health centers. Self-care (SCODI) and QoL (DQOL) were measured using validated questionnaires, and HbA1c, blood pressure, and BMI were obtained from clinical records. Structural equation modeling (SEM) was conducted using IBM AMOS version 24. Results: The SEM analysis yielded an overidentified model (df = 1578) with acceptable fit indices (CFI = 0.908, RMSEA = 0.082, CMIN/df = 1.851). Self-maintenance significantly predicted QoL, HbA1c, and blood pressure. Self-monitoring reduced blood pressure and BMI but was negatively associated with QoL. Self-management improved HbA1c but increased blood pressure and BMI, with a borderline positive effect on QoL. Self-confidence was positively associated with BMI but not with QoL, HbA1c, or blood pressure. Among physiological indicators, only HbA1c significantly predicted QoL. Conclusion: The direct effects of self-care behaviors on quality of life were more significant than the indirect effects mediated by clinical indicators, emphasizing the importance of strengthening daily self-care skills as a core strategy to enhance well-being in patients with T2DM. Given the exploratory cross-sectional design, findings should be interpreted as associative rather than causal. Future longitudinal research should validate these pathways and develop culturally sensitive intervention models that empower patients to sustain effective self-care behaviors over time.